Library Web site usability: what, why and how? - Vrana, Radovan (2003)
Owing to the evolution of libraries towards their digital variants and fast spread of information technology in general, libraries are now accessible on the Internet in greater number than ever before. Many of them have enhanced their existing services accessible locally in the library by offering their equivalents online on the Web, while others are building new and more complex interactive and Web application supported sites. The main reason why people visit library Web sites is that they are looking for specific information, and as a result of this it has become crucial that the library Web site is well organized, information properly categorized, labeled and presented, and that adequate navigation and information access systems are provided. Libraries usually don't have specially trained employees having sufficient knowledge about human-computer interaction, and skills in building complex Web sites including ergonomic user interfaces and database supported Web applications. Current situation on the Internet indicates substantial number of different approaches in library Web site development, which causes problems to library users not prepared and willing to switch between growing number of different directories, interactive menus, WebPAC interfaces, or search engines. More broadly observed, while building their Web sites libraries are facing a number of challenges in several areas (Cunliffe, 2000): Limited financial resources Limited development team Lack of knowledge and skills of building interactive services Diverse user population Lack of clear model of user behavior Blending of Web site design elements (content, visual appearance and usability) Dynamic open-ended publication (Web site can't ever be considered for "a finished product" The wide range and variable quality of guidance available etc. This is by no means the definitive list of problem areas, but it describes some of the common problems shared among libraries wishing to expand their presence on the Internet very well. Fortunately, there is an area of human-computer interaction covering topic known as usability, which could help many librarians to plan and design library Web sites based on common principles guaranteeing easier and more successful access to information and services presented by libraries on the Web sites of their own libraries. The term usability can be defined (ISO 9241 definition) as the effectiveness, efficiency and satisfaction with which specified users achieve specified goals in particular environments. Effectiveness means the accuracy and completeness with which specified users can achieve specified goals in particular environments. Efficiency means the resources expended in relation to the accuracy and completeness of goals achieved. (User) Satisfaction: the comfort and acceptability of the work system to its users and other people affected by its use. In their efforts to achieve usability, librarians can refer to the existing studies and guidelines describing methods and procedures for good Web design which include categories such as (Turner, 2002): Navigation Page design Content Accessibility Media use Interactivity Consistency. These categories also represent points where library Web site design usually fails. In light of the described problems, this poster will give an overview of theoretical and practical key points in planning and design of library Web sites, and present a set of Web site usability guidelines applicable in library Web site development.
Projekt MZOS
ENG